Parents’ Levels of Satisfaction With Early Childhood Service Quality: Insights From Guyana (Journal of Education and Development, 2023)
Understanding parents’ satisfaction with quality is necessary for offering services that better meet the needs of children and families. However, there is a paucity of such research in Guyana. Through a descriptive survey, 51 parents provided insights to guide decisions about service at the University of Guyana Early Childhood Centre of Excellence. Five areas of service quality identified by the Caribbean Community policy-making body on effective early childhood settings were examined: programme participation, staff engagement, management and administration, parent/family partnership, and health and safety. Over 90% of the responses about the quality of service were positive, indicative of influence by the detailed self-administered questionnaire. Negative responses, especially by parents of the youngest groups of children, suggest there are elements of services that are not adequately met, acceptable, or sufficiently visible to some parents. Being the first research of this kind in Guyana, early childhood service providers, and other stakeholders might find the parents’ recognition and interpretation of quality informative and a reference point for considering critical issues concerning quality provision for young children.